PEMETAAN ZONA AGROKLIMAT SCHMIDT FERGUSON MENGGUNAKAN DATA STASIUN PENGAMAT HUJAN DAN PRODUK DATA SATELIT IMERG DI PROVINSI BALI - Wahyu Widodo Putranto; I Wayan Nuarsa; Ni Luh Kartini; I Wayan Andi Yuda; I Made Dwi Wiratmaja (Master Program of Environmental Science, Postgraduate Program of Udayana University, 2022)
Schmidt Ferguson map based on rainfall data is utilized to maximize agricultural potential by knowing the spatial pattern of agro-climatic zones. This study aims to produce Schmidt Ferguson agro-climatic zone by corrected IMERG Satellite rainfall data by station base data in Bali Province. The length of monthly rainfall data from each source is six years (2015 – 2016). Initially, IMERG Final Precipitation data level 3 is validated to 73 rainfall observation stations over Bali. Statistical methods used for this purpose are correlation coefficient (r), Root Mean Square Error (RMSE) and paired t-test. The validation results show a good correlation value of 0.62 – 0.93, RMSE value of 63.33 – 208.86 mm, the results of the paired t-test there are significant. Hereinafter, IMERG data are corrected by simple linear regression equation y = 0.905x + 4.0979 with an R2 value of 0.5878. The Schmidt Ferguson agro-climatic zone mapping from rain observation station data resulted in 5 climate zones, namely climate zone B, C, D, E, and F and from IMERG product data, 4 climate zones, namely climate zone B, C, D, and E. Keywords: Observation; IMERG;Data Validation; Schmidt Ferguson Agroclimate Zone